Summer state of mind [large type] - Harvey, Kristy Woodson (Center Point Large Print, 2026)
"After the worst day in her professional life, burnt-out NICU nurse Daisy Stevens runs to Cape Carolina, North Carolina, looking for a new life -- and possibly new romance. On her first day at her "simpler" job, high school baseball coach Mason Thaysden discovers an abandoned baby, sending ripples through the entire tight-knit town of Cape Carolina. Mason is still struggling to reconcile the scars of the injury that kept him out of the big leagues, stuck in his hometown, and searching for a way out. This newcomer and the child they've saved together might be just the motivation he needs to stay put. Sparks fly as Mason acquaints Daisy with Cape Carolina, introducing her to his friends and family, including his batty Aunt Tilley, who is looking for relief from long-buried family secrets and her own fresh start. But as Daisy becomes increasingly attached to this abandoned child, and begins facing her own demons in the process, a startling discovery is made that threatens to rip the entire town of Cape Carolina apart, placing Daisy, Mason, and Tilley in the center of the storm."--